Ventilation Weaning and Extubation Readiness in Children in Pediatric Intensive Care Unit: A Review - Poletto, Elisa; Cavagnero, Francesca; Pettenazzo, Marco; Visentin, Davide; Zanatta, Laura; Zoppelletto, Fabrizio; Pettenazzo, Andrea; Daverio, Marco; Bonardi, Claudia Maria (Frontiers in Pediatrics, 2022)
Ventilation is one of the most common procedures in critically ill children admitted to the pediatric intensive care units (PICUs) and is associated with potential severe side effects. The longer the mechanical ventilation, the higher the risk of infections, mortality, morbidity and length of stay. Protocol-based approaches to ventilation weaning could have potential benefit in assisting the physicians in the weaning process but, in pediatrics, clear significant outcome difference related to their use has yet to be shown. Extubation failure occurs in up to 20% of patients in PICU with evidences demonstrating its occurrence related to a worse patient outcome including higher mortality. Various clinical approaches have been described to decide the best timing for extubation which can usually be achieved by performing a spontaneous breathing trial before the extubation. No clear evidence is available over which technique best predicts extubation failure. Within this review we summarize the current strategies of ventilation weaning and extubation readiness evaluation employed in the pediatric setting in order to provide an updated view on the topic to guide intensive care physicians in daily clinical practice. We performed a thorough literature search of main online scientific databases to identify principal studies evaluating different strategies of ventilation weaning and extubation readiness including pediatric patients receiving mechanical ventilation. Various strategies are available in the literature both for ventilation weaning and extubation readiness assessment with unclear clear data supporting the superiority of any approach over the others.